Fall River outrage : life, murder, and justice in early industrial New England - Kasserman, David Richard (UPCC book collections on Project MUSE., 1986)
Fall River Outrage recounts one of the most sensational and widely reported murder cases in early nineteenth-century America. When, in 1832, a pregnant mill worker was found hanged, the investigation implicated a prominent Methodist minister. Fearing adverse publicity, both the industrialists of Fall River and the New England Conference of the Methodist Episcopal Church engaged in energetic campaigns to obtain a favorable verdict. It was also one of the earliest attempts by American lawyers to prove their client innocent by assassinating the moral character of the female victim. Fall River Outrage provides insight in American social, legal, and labor history as well as women's studies.